Community Resilience : a critical approach - Wright, Katy (New York: Routledge, 2022)
"This book provides an alternative perspective on community resilience, drawing on critical sociological and social policy insights about how people individually and collectively cope with different kinds of adversity. Based on the idea that resilience is more than simply an invention of neoliberal governments, this book explores diverse expressions of resilience and considers what supports and undermines people's resilience in different contexts. Focusing on the UK, it examines the contradictions and limitations of neoliberal resilience policies and the role of policy in shaping how vulnerabilities are distributed and how resilience is manifested. The book explores resilience by looking at different types of resilience from anticipatory planning, through response and recovery to adaptation and transformation, explored in relation to different types of threat such as financial hardship, disasters and climate change. It argues that resilience cannot act as an antidote to vulnerability, and aims to demonstrate the importance of shared institutions in underpinning resilience and in preventing socially created vulnerabilities. It will be of interest to academics, students and well-informed practitioners working with the concept of resilience within the subject areas of Sociology, Social Policy, Human Geography, Environmental Humanities and International Development"-- Provided by publisher.
Introduction -- Resilience -- Risk -- Community, Cohesion and Organisations -- Preparation and Planning -- Response and Recovery -- Adaptation and transformation -- Community Resilience in the Covid-19 Pandemic -- Conclusion.